The effect of swirl number on reducing emissions from liquid fuel burner system - Ashrul Ishak, Mohamad Shaiful (Universiti Teknologi Malaysia, Faculty of Mechanical Engineering, 2005)
The release of gaseous emissions such as oxides of nitrogen (NOX), and carbon monoxide (CO) into the atmosphere creates major environmental problems. These gaseous emissions affect plants, human being and animals. High concentration of emissions brings fatal effects to life form. A liquid fuel burner system with different radial air swirler vane angles with 280 mm inside diameter combustor of 1000 mm length has been investigated. All tests were conducted using diesel as fuel. A radial flow air swirler with curved blades having 50 mm outlet diameter was inserted at the inlet plane of the combustor to produce swirling flow. Fuel was injected at the back plate of the swirler outlet using central fuel injector with single fuel nozzle pointing axially outwards. The swirler vane angles and equivalence ratios were varied. Tests were carried out using eight different air swirlers having 10°, 20°, 30°, 40°, 45°, 50°, 60° and 70° vane angles. NOX reduction of more than 26 percent was obtained for the swirl number of 1.427 compared to 0.046. A turning point occurs at this stage where the emission of NOX suddenly increases about 23 percent when swirl number of 1.911. CO emissions were reduced by 33 percent, 40 percent and 48 percent reduction in carbon monoxide (CO) emission for swirl number of 0.978, 1.427 and 1.911 respectively compared to swirl number of 0.046. Meanwhile, CO2 have a stable distribution of emissions for the whole range of equivalence ratios. However, CO2 emission increases when higher vane angle swirlers were used. CO2 emissions of about 11.6 percent, 11.7 percent and 15.5 percent decrease for swirl number of 0.978, 1.427 and 1.911 respectively, compared to swirl number of 0.046 at the equivalence ratio of 0.833.